Characteristics of H3K27M-mutant diffuse gliomas with a non-midline location - Guidara, Souhir; Seyve, Antoine; Poncet, Delphine; Leonce, Camille; Bringuier, Pierre-Paul; McLeer, Anne; Sturm, Dominik; Cartalat, Stéphanie; Picart, Thiebaud; Ferrari, Anthony; Hench, Jürgen; Frank, Stephan; et al. (Journal of neuro-oncology, 2024)
Diffuse midline gliomas (DMG) with H3K27 alterations (H3K27M-DMG) are a highly aggressive form of brain cancer. In rare cases, H3K27 mutations have been observed in diffuse non-midline gliomas (DNMG). It is currently unclear how these tumors should be classified. Herein, we analyze the characteristics of DNMG with H3K27M mutations.